Comparative Study of Winter and Summer Fodder Species and Their Mixtures on-Station and on-Farm Conditions - Ghimire, Ram Prasad; Tiwari, Megh Raj; Amgain, Rita; Pariyar, Dinesh; Shrestha, Kishor Kumar (Nepalese Journal of Agricultural Sciences, 2026)
Cultivated fodder species and cereal-legume mixtures can boost fodder supply, enhance nutritive value, and decrease reliance on crop residues, thereby helping to address the severe feed shortage faced by ruminant livestock in Nepal. This study aimed to evaluate winter and summer fodders and their mixtures under on station conditions and verify them across diverse agro-ecological regions. In the first year, 12 winter and eight summer fodder treatments—including sole cereals, sole legumes, and mixtures—were tested in separate experiments at the National Pasture and Fodder Research Program, Khumaltar. Both winter and summer trials used a Randomized Complete Block Design with three replications. Based on first-year performance, one winter package (Oat + Berseem) and one summer package (Teosinte + Cowpea) were selected for farmers’ field tests in four districts: Dhading, Kabhrepalanchowk, Banke, and Sunsari. Data on dry matter yield and related attributes were analyzed using ANOVA and Tukey’s Honest Significant Difference Test at the 5% significance level. On-station results showed that sole Oat (Avena sativa) produced the highest (p<0.001) winter dry matter yield (15.63 t/ha), and the Oat + Berseem (Trifolium alexandrium) mixtureyielded similarly (14.82 t/ha; (p>0.05)). Among summer fodders, Teosinte(Euchlaena mexicana) + Cowpea (Vigna unguiculata) achieved the highest yield (22.74 t/ha). In the second year’s on-farm experiments, Oat + Berseem yielded the highest in Banke (14.95 t/ha) and the lowest in Kabhrepalanchowk (6.18 t/ha), while Teosinte + Cowpea also produced the best yield in Banke (27.65 t/ha). These results indicate that Oat + Berseem and Teosinte + Cowpea are suitable package options across locations for year-round fodder production to improve livestock productivity